2013
DOI: 10.1007/s11325-013-0918-0
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and body mass index in children and adolescents with and without obstructive sleep apnea

Abstract: A parental history of total sleep duration of only 1 h less than recommended per age by the NSF is associated with a higher risk for obesity in children independently of the presence of OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…However, it was found lower in overweight and obese students when compared to normal weight students. Epidemiological studies have reported a relation between short sleep duration and excessive body weight [22,23]. Sleep duration has been defined among risks for being overweight in childhood and adolescent periods.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found lower in overweight and obese students when compared to normal weight students. Epidemiological studies have reported a relation between short sleep duration and excessive body weight [22,23]. Sleep duration has been defined among risks for being overweight in childhood and adolescent periods.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the child needs to go to bed before 8:30 pm to get more than 11 hr of sufficient sleep (i.e. age-appropriate bedtimes); bedtimes between 8:30 and 9:30 pm may translate to 10-11 hr of sleep and are thus borderline bedtimes [17][18][19]. Similarly, a 9-year-old who needs to be at school by 8:00 am might awaken about 7:00 am, meaning the child needs to go to bed before 9:00 pm to have more than the minimum of 10 hr of sufficient sleep [19].…”
Section: Presence and Timing Of Bedtimesmentioning
confidence: 99%
“…At the age 5 and 9 interviews, mothers were asked "How many hours of sleep a night does your child usually get during the week (integer hours)?" Age-appropriate sufficient sleep was defined as 11 hr or more sleep/night for 5-year-old and 10 hr or more sleep/night for 9-year-old [17][18][19]. Borderline sleep was when sleep duration was within 1 hr of the recommended amount for that age (10-11 hr/night at age 5 and 9-10 hr/night at age 9).…”
Section: Sleep Durationmentioning
confidence: 99%
“…These effects include an increased risk of cardiovascular disease and factors related to metabolic abnormalities, such as dyslipidemia, glucose intolerance and an increased likelihood of being obese as an adult 2 . Other symptoms such as sleep apnea 3,4 as well as psychological and social repercussions have been reported in the literature 5 .…”
Section: Introductionmentioning
confidence: 98%